Fatigue in familial Mediterranean fever and its relations with other clinical parameters - ÜNAL, ÇAĞRI; DURUÖZ, MEHMET TUNCAY (SPRINGER HEIDELBERG, 2018)
Fatigue is a common problem in patients with rheumatic disease. It may cause disability and poor quality of life. The aim of this study is to investigate fatigue in FMF patients as a disabling symptom and its associations with clinical and demographic variables. FMF patients were recruited into the study according to FMF Tel Hashomer criteria. Control group is composed of healthy individuals. Demographic and clinical features of the patients including PRAS scores were noted. Visual analogue score of pain (VAS-pain) and VAS-fatigue were used as clinical parameters. Pittsburgh Sleep Quality Index (PSQI), Multidimensional Assessment of Fatigue (MAF), Nottingham Health Profile (NHP), Fatigue Severity Scale (FSS), Fatigue Impact Scale (FIS) and Hospital Anxiety and Depression Scale (HADS) were filled out by both control and study group. Sixty-one FMF patients and 61 age and gender (44 female, 17 male in each group)-matched controls were enrolled into the study. Mean age of FMF and control group were 35.5 +/- 11.8 and 35.8 +/- 11.7 years, respectively. The mean disease duration was 82.5 +/- 81.7 months. Difference between mean of VAS-pain, VAS-fatigue, PSQI total score, MAF, all subsets of NHP, FSS, FIS, and HADS scores of FMF patients was significantly higher than of control group (p = 0.0001). This study has shown that fatigue in FMF is associated with a number of psychological, sleep, quality of life and disease-related factors. FMF group had increased pain, fatigue, sleep disturbance and decreased quality of life compared to control group. FMF patients with fatigue may benefit from pharmacological and psychological interventions which target these factors.
Keywords: Familial Mediterranean fever; Fatigue; Fatigue in rheumatic diseases; Orphan diseases; Quality of life; QUALITY-OF-LIFE; SYSTEMIC-LUPUS-ERYTHEMATOSUS; RHEUMATOID-ARTHRITIS; DISEASE-ACTIVITY; SLEEP QUALITY; DEPRESSION; SCALE; PAIN; FIBROMYALGIA; ASSOCIATIONS